2019
DOI: 10.18311/ajprhc/2019/24915
|View full text |Cite
|
Sign up to set email alerts
|

Injury Prevalence, Types and Mechanisms in Football: A Media-based Approach

Abstract: The increase in demand for football players to perform at their best during training and competition results in the escalation of a varying number of football-related injuries. Media reports provide readily as well as timely information on injury-related issues that could assist the stakeholders in decision making before and after a competition. Although, many attempts have been made to quantify football-related injuries in many countries via media, however, little is known on its prevalence, types and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
2
0
6
Order By: Relevance
“…Additionally, robust methods of injury data collection are required to allow for sophisticated analysis of tennis-related injuries [ 9 ]. In this regard, research has shown the importance of mainstream media, particularly newspapers, in providing useful data for injury analysis [ 10 , 11 ]. It has also been reported that newspapers cover more injury-related events than other sources [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, robust methods of injury data collection are required to allow for sophisticated analysis of tennis-related injuries [ 9 ]. In this regard, research has shown the importance of mainstream media, particularly newspapers, in providing useful data for injury analysis [ 10 , 11 ]. It has also been reported that newspapers cover more injury-related events than other sources [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, effective injury data gathering methods are necessary to enable extensive research of tennis-related injuries ( 9 ). In this context, studies have demonstrated that mainstream media, particularly newspapers, are important in offering helpful data for injury analysis ( 10 , 11 ). Newspapers have been observed to report more injury-associated occurrences as compared to other media ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, os administradores estão gradualmente preocupados em serem responsabilizados pela segurança e bem-estar dos jogadores de futebol (ANDERSON; KIAN, 2012). Dada a importância do futebol na promoção da saúde e do bem-estar físico (FORTINGTON et al, 2018), é necessária uma análise adequada dos padrões e tendências das lesões (FORTINGTON;FINCH, 2016;MUSA et al,2019).…”
Section: Introductionunclassified
“…O conteúdo da mídia fornece dados oportunos e confiáveis sobre lesões no futebol, que podem ajudar as partes interessadas na tomada de decisões, especialmente antes ou depois das competições (MUSA et al, 2019). Uma vez ocorridas as lesões no futebol, é provável que elas sejam relatadas como eventos dignos de notícia.…”
Section: Introductionunclassified
See 1 more Smart Citation